Effect of Hibiscus rosasinensis on the liver of Swiss albino mice: a histo-morphological investigation (Progressive Agriculture, 2016)
Nature has been a source of medicinal agents for the thousands of years and a large number of drugs have been isolated from natural sources. Over 50% of all modern drugs are originated from natural sources. Hibiscus rosasinensis is also a very renowned flower having a vast use as a medicinal plant. Several studies have shown that the flower, leaf of this plant has a wide range of medicinal uses such as contraception, anti-nociceptive, anti-inflammatory, anti-allergic, anti-tumor, anti-diarrheic and anti-convulsent. But whether this plant affects the liver or not is still not investigated with proper care. For the sake of this purpose a research was conducted on the Swiss albino mice in the Bioresearch Laboratory, Department of Anatomy and Histology, Bangladesh Agricultural University, Mymensingh-2202. Twenty (20) mice (Avg. weight of 27-28 gm and avg. age of 6-7 weeks) were purchased from ICDDRB, Mahakhali, Dhaka and divided into two groups (control, C and Treated, T) each having 10 mice. During the experimental period, the control group was supplied with the normal mice pellet and plane water whereas, the powder of the Hibiscus rosasinensis @ 500 mg/ml with drinking water and the normal mice pellet was provided to the treated group. After the end of the experimental tenure of one month the mice were sacrificed ethically and sample (liver) was collected for the gross and histological analysis. Both in the gross and histology the histomorphology of the liver was similar without having any alteration from the normal. No remarkable changes of the gross and histological architecture were found. So it can be said that the extract of Hibiscus rosasinensis has no baleful effects on the histomorphology of the liver in Swiss Albino mice.Progressive Agriculture 27 (3): 296-300, 2016